In the Service of the Local Elite: The Career of István Berzeviczy and His Attachment to Ung County - Varga, Róbert (Вісник гуманітарних наук, 2025)
This study aims to present the life and career of István Berzeviczy between 1893 and 1916. It describes his years as police chief, his political and cultural activities, and his social connections. Special attention is paid to the relationships he developed with the leading elite of the county, which influenced his career and public role. Objective. This study seeks to explore the career of police chief István Berzeviczy and his ties to Ung County between 1893 and 1916, with particular emphasis on his official duties and his social and political involvement. The primary goal of the research is to shed light on the local operations of the police force and Berzeviczy's role in the administration and cultural life of the city of Uzhhorod. Methods. The research is based on the processing of fonds stored in the Beregszász branch of the Carpathian State Archives. During my research, I explored sources in fonds 6 (the documents of the mayor’s office of the statutory city of Uzhhorod) and fonds 7 (documents of the sub-prefect of Ung County). Among the contemporary documents, I found correspondence, instructions, and reports related to István Berzeviczy. The archival research was supplemented by a source-critical analysis of contemporary press publications – Ung, Határszéli Újság, Az Újság, Görögkatolikus Szemle – as well as oral history derived from family memories. Results. Research on the subject has revealed that high-ranking patrons played an important role in István Berzeviczy's career advancement, but at the same time, according to contemporary opinions, he also needed to be capable of leading a well-functioning police force during his term of office. During his tenure as police chief, the Uzhhorod City Police operated within a structured framework, and besides maintaining public order, they were increasingly tasked with safeguarding political loyalty. István Berzeviczy gradually became involved in the social and cultural life of the county. Through his wide-ranging public activities, he contributed greatly to shaping the social and cultural life of the city of Uzhhorod. According to contemporary press reports, his reputation was somewhat mixed: on the one hand, his high level of administrative competence was recognized, but on the other hand, he was also seen as a powerful figure serving the interests of the local elite. Conclusions. In this study, I present the life and career of István Berzeviczy, paying particular attention to his roles as police chief, politician, and cultural figure. My research shows that Berzeviczy successfully led the Uzhhorod City Police: under his leadership, public order and safety in the city became more stable. According to archival sources and contemporary press reports, he received significant support from influential local families—the Török, Kende, and Sztáray families—who played a crucial role in shaping his later political career. His loyalty to the Ung elite was particularly evident in his role in the coup against Chief Magistrate Zsigmond Bernáth. This commitment proved to be worthwhile: he became the leading candidate for the vacant position of mayor of Uzhhorod, and, having won the majority of votes, served as mayor of Uzhhorod from 1916 to 1919. In addition to his official duties, Berzeviczy was also actively involved in the social and cultural life of the city: in 1910, he was elected president of the Uzhhorod Athletic Club, and from 1916, he served as president of the Uzhhorod Social Circle. In addition, in 1911, he presented his poetry collection at an event for amateur writers and readers in Gyöngyös.